Out of the Picture: Latinx and White Male Youths’ Facial Features Predict Their Juvenile Justice System Processing Outcomes - Chen, Jacqueline M. (Crime & delinquency, 2021)
Adults’ facial characteristics predict whether and how severely they are sentenced in the adult criminal justice system. We investigate whether characteristics of White and Latinx male youths’ faces predict the severity of their processing in the juvenile justice system. Among a sample of first-time offenders, despite no differences in the severity of their offenses, youth who were perceived by naïve observers as more dominant, less trustworthy, less healthy, and having darker skin were more likely to receive harsher sanctions. Thus, extralegal factors like appearance may bias legal decisions that place some youth at increased risk for more restrictive sanctioning. Our findings highlight the need for structured approaches to juvenile processing decisions that take youths’ appearance out of the picture.